(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2023)
Questions: How high is the diversity of the lichen-forming, lichenicolous and lichen-related fungi in Teremky woodland? How reprentative is the old-growth oak forest by Indicators of Ecological Continuity for the woodland? Location: Kyiv Region, Ukraine Materials and methods: аbout 80% of the observations were made during the autumn-winter blackout within 3 hours in the woodland per day; microscope technique Nomenclature: Index Fungorum, POWO 2023, Mucina et al. 2016 Results: The list of 126 species of lichen-forming, lichenicolous fungi and lichen-related fungi from 75 genera, 32 families, 19 orders, 8 classes and 2 divisions have been provided for the Teremky woodland as a part of the Holosiivskyi National Nature Park (Kyiv, Ukraine). Lichen-forming fungi are represented by 105 species, lichenicolous fungi – by 13 species, and lichen-related fungi (facultative lichens or semi-lichens) – by 8 species. Among them 54 species of lichens, lichenicolous and lichen-related fungi are new for the Holosiivskyi National Nature Park, 35 species new to the Kyiv region, 10 species new to the lowland part of Ukraine and three species new to Ukraine. Corticolous lichen species (101 species, 84%) are predominantly found in the Teremky woodland. It is highest representation on Quercus robur (72 species), but the peculiarity of the woodland is the presence of a significant number of old-growth Prunus avium trees with 44 corticolous species. The most abundant lichens (more then 11 locations) in the Teremky woodland are 19 species (15%), while more than half of the species (71 species, 56%) are rare (1–3 locations). Eight indicator species of the ecological continuity for woodland as Acrocordia gemmata, Anisomeridium biforme, Bactrospora dryina, Bacidia rubella, Chaenotheca phaeocephala, Ch. trichialis, Eopyrenula leucoplaca, Toniniopsis separabilis were found in the Teremky woodland, which is sufficient to indicate high representativeness (category B) of Central- European hornbeam-oak habitats. The maximum diversity of corticolous lichen-forming, lichenicolous and lichen-related fungi is 63 species per hectare, which can be used as a baseline for comparison with other forest habitats of the plain part of Ukraine.The indicator qualities of corticolous lichen-forming fungi are discussed.